Microfinance Poverty Assessment Tool - Henry, Carla; Sharma, Manohar; Lapenu, Cecile; Zeller, Manfred (Washington, DC: World Bank and CGAP, 2013)
Currently, no rigorous tool exists to measure the poverty level of microfinance institution (MFI) clients. In order to gain more transparency on the depth of poverty outreach, CGAP collaborated with the International Food Policy Research Institute (IFPRI) to design and test a simple, low-cost operational tool to measure the poverty level of MFI clients relative to nonclients. This tool is a companion piece to the CGAP Appraisal Format; donors should not use the poverty assessment tool without also conducting a larger institutional appraisal. The concept of poverty is complex and strongly influenced by local cultural and socioeconomic conditions. The poverty assessment approach presented in this manual supports a flexible definition of poverty that can be adapted to fit local perceptions and conditions of poverty. The tool is intended neither as a means to target new clients nor to assess the impact of microfinance services on the lives of existing clients. It may provide a useful means to verify-both for the donor and the MFI-the extent to which an existing strategy results in poor clients joining the MFI. The tool assesses the poverty levels of MFI clients compared to nonclients within the operational area of an MFI. Using available data or expert opinion, the tool also relates local poverty levels to poverty measured at larger regional and national levels.